The girl who escaped ISIS : this is my story / Farida Khalaf and Andrea C. Hoffmann translated from the German by Jamie Bulloch. - Khalaf, Farida; Hoffmann, Andrea Claudia (Atria Books, 2016)
"A rare and riveting first-hand account of the terror and torture inflicted by ISIS on young Iraqi Yazidi women, and an inspiring personal story of bravery and resilience in the face of unspeakable horrors. In the early summer of 2014, Farida Khalaf was a typical Yazidi teenager living with her parents and three brothers in her village in the mountains of Northern Iraq. In one horrific day, she lost everything: ISIS invaded her village, destroyed her family, and sold her into sexual slavery. The Girl Who Escaped ISIS is her incredible account of captivity and describes how she defied the odds and escaped a life of torture, in order to share her story with the world. Devastating and inspiring, this is an astonishing, intimate account of courage and hope in the face of appalling violence"--